Seroprevalence of anti- C. trachomatis IgG and IgM antibodies Among Pregnant women in Diyala province - Hwaid, Asmaa H.; Hasan, Abul-Razak SH.; Al-Duliami, Abbas A. (Journal of the Faculty of Medicine Baghdad, 2014)
Background: Chlamydia trachomatis infections are the most prevalent bacterial sexually transmitted infections (STI) recognized throughout the world. Screening programs for C. trachomatis is of paramount importance in the prevention of long-term sequelae.Subjects and methods: A total of 91 normal healthy women were included in this study, which was conducted for the period from 1st. November/ 2011 to 1st. March 2012. They were chosen by simple random selection from Al-Batool Teaching Hospital for maternity and children, and some health care centers in Baquba city. The age range was 17-42 years. 49 (53.8%) and 42 (46.1%) were from rural and urban areas respectively. 77 (84.6%) of women with no previous abortion, and 14 (15.3%) with one or more abortions. 15 (16.5%) with no previous deliveries, and 76 (83.5%) had a number of children ranging from 1 to 7. The anti-chlamydia IgG and anti-chlamydia IgM antibodies were detected using ELISA technique.  Statistical analysis was performed using SPSS version -15, and P - value of < 0.05 was considered significance.Objectives: To investigate the anti-chlamydia IgG and IgM seropositivity of healthy pregnant women in Baquba-Diyala province.Results: The results revealed that the rate of anti-chlamydia IgG antibody among pregnant women was 5(5.5%), and 3 (3.3%) women were positive for anti-chlamydia IgM antibody. All anti-chlamydia IgM and the majority of anti-chlamydia IgG antibody positive women were belong to the age group 20-29 years. The anti-chlamydia IgM and IgG positivity rate has no association with residency, number of children, number of previous abortions, and the duration of pregnancy.Conclusion: The rate of C. trachomatis infection among healthy pregnant women in diyala province was low.